Age and gender differences in the relationship between obesity and disability with self-perceived employment discrimination: Results from a retrospective study of an Australian national sample - Keramat, Syed Afroz; Alam, Khorshed; Rana, Rezwanul Hasan; Shuvo, Suvasish Das; Gow, Jeff; Biddle, Stuart J H; Keating, Byron (My University, 2021)
Background Health status is a crucial determinant of an individuals’ labour market outcomes. The present study investigates the association between obesity and disability with perceived employment discrimination within Australia. Methods A total of 17,174 person-year observations from the 11,079 respondents were analysed using four waves of data from the Household, Income, and Labour Dynamics in Australia (HILDA) survey. The primary outcome examined was employment discrimination, using obesity and disability as the main exposure variables. The longitudinal random-effects regression technique was applied to investigate the between-person differences in employment discrimination associated with obesity and disability. Results The findings suggest that more than one in ten (12.68 %) Australians experienced employment discrimination. The odds of being discriminated against while applying for a job were 1.56 times (aOR: 1.56, 95 % CI: 1.15–2.11) higher for obese than their healthy weight counterparts in youngest women. Adults with a disability had 1.89 times (aOR: 1.89, 95 % CI: 1.65–2.17) higher odds of being discriminated against than peers without disability. Conclusion The results provide evidence that obesity and disability contribute to employment discrimination in Australia. The findings can assist government and related agencies to consider the adequacy of existing discrimination legislation and help organisations to develop appropriate policies to address discrimination against obese and disabled people in their workplaces.
SSM - Population Health
Keywords: Australia; Disability; Employment discrimination; HILDA; Obesity; Disadvantage, adversity and resilience; Health and wellbeing; Labour market